PERSEPSI JEMAAT TERHADAP IBADAH MINGGU LIVE STREAMING GEREJA KALIMANTAN EVANGELIS (GKE) EPPATA BANJARMASIN - Keloso S. Ugak; Alexandra Binti; Hendra; Wahyuno (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2021)
The purpose of this research is to analyze and describe the congregation's perception of Sunday worship by live streaming in the church of GKE Eppata Banjarmasin during the COVID 19 pandemic. This research type is explanatory research by quantitative approach. Primary data collection to make use of an online questionnaire (google form application). Respondents were taken by non-random sampling and a deadline for distributing and filling out the questionnaire. 40 members of the GKE Eppata Banjarmasin Congregation who participated filled out an online questionnaire. The data analysis for determining the effect of the congregation's perception, as an exogenous variable (X) on Sunday worship, live streaming endogenous variable (Y), make use of Partial Least Square (PLS) analysis technique with SmartPLS 3.0 software. Through the results of this research can be concluded that the perception of the congregation (X) had a positive and significant effect on the live streaming Sunday worship (Y). This shows that the perception of the congregation, during the COVID-19 pandemic towards the live streaming Sunday worship, has a strong relationship. The susceptibilities of this research are not varied in terms of age, gender in relation to the sample of respondents, and could not make sure the number of respondents because of limited time for distributing questionnaires and social distancing restrictions.